Clinical evaluation of a composite resin and a resin-modified glass-ionomer cement in non -carious cervical lesions: one year result - Oliveira, Fernanda Garcia de; Machado, Lucas Silveira; Rocha, Eduardo Passo; Alexandre, R A; Fraga, Briso André Luiz; Sundefeld, Maria Lucia Maçal Mazza; Sundfeld, Renato Herman [UNESP] (My University, 2011)
Objectives: The objective of this study was to evaluate the clinical performance of 124 non-carious cervical lesion restorations at 12 months. Materials And Methods: Three study groups were formed according to the material and technique used. All teeth received 37% phosphoric acid etching in enamel and dentin. The teeth of Group I received the conventional adhesive system Scotch Bond Multi Purpose, followed by resin composite Filtek Z350; teeth of Group II were restored with resin-modified glass-ionomer cement Fuji II LC; teeth of Group III were restored with the same resin-modified glass-ionomer cement however, before it was inserted, 2 coats of primer of the Scotch Bond Multi Purpose adhesive system were applied to dentinal tissue. The teeth were evaluated by 2 examiners with regard to the factors of retention, marginal adaptation, marginal discoloration, color alteration, presence of marginal caries lesion, anatomic shape, and sensitivity. Results: Application of the Kruskal-Wallis test showed no statistically significant difference for anatomic shape, marginal discoloration, color alteration, caries lesion, marginal adaptation, and sensitivity among the three study groups, but the variable retention presented statistically significant difference at 12 months, with Group III presenting a behavior superior to that of Group II but similar to that of Group I. Conclusion: The analyzed restorations of non-carious cervical lesions presented a good clinical performance at 12 months.
Keywords: Análise clínica longitudinal; IOnômero de vidro fotoativado